Dismantling the Nation Contemporary Art in Chile - San Martín, Florencia; Macchiavello Cornejo, Carla; Solimano, Paula (Amherst College Press, 2023)
The first academic volume to theorize and historicize contemporary artistic practices and culture from Chile in the English language, Dismantling the Nation takes as its point of departure a radical criticism against the nation-state of Chile and its colonial, capitalist, heteronormative, and extractivist rule, proposing otherwise forms of inhabiting, creating, and relating in a more fluid, contingent, ecocritical, feminist, and caring worlds. From the case of Chile, the book expands the scholarly discussion around decolonial methodologies, attending to artistic practices and discourses from distinct and distant locations-from Arica and the Atacama Desert to Wallmapu and Tierra del Fuego, and from the Central Valley, the Pacific coast, and the Andes to territories beyond the nation's modern geographical borders. Analyzing how these practices refer to issues such as the environmental and cultural impact of extractivism, as well as memory, trauma, collectivity, and resistance towards neoliberal totality, the volume contributes to the fields of art history and visual culture, memory, ethnic, gender, and Indigenous studies, filmmaking, critical geography, and literature in Chile, Latin America, and other regions of the world, envisioning art history and visual culture from a transnational and transdisciplinary perspective.